Analysis Of The Role Of Accounting Information Systems Ineffectiveness Value And Efficiency Of Preparation Financial Reports At Spbu Office 74.916.66 Tanrutedong - Nurul Mutiara; Hernianti Harun (Journal AK-99, 2023)
This study aims to determine the role of accounting information systems in decision making and to determine the value of the effectiveness and efficiency of financial reports at the Tanrutedong gas station 74.916.66 as measured by the level of effectiveness and efficiency ratio. The data collection techniques used in this study were observation, interviews, and documentation. . The type of this research is qualitative. The data analysis technique in this research is descriptive research. The results of the research that has been carried out are the role of accounting information systems in decision making at the Tanrutedong gas station 74.916.66 Accounting information systems play an important role in producing financial report information for the benefit of external parties. The information system also collects information on financial issues for the preparation of financial reports effectively and efficiency. SPBU 74.916.66 Tanrutedong in preparing the financial reports the system module used is the SUMEH application which is an online gas station financial digitization program. The financial reports used with the accounting information system show effective and highly efficient results for the last three years, namely 2020 to 2022 at the Tanrutedong gas station office 74.916.66.